COMBINATION METHOD OF ADVANCED OXIDATION PROCESS (AOPs) AND ELECTROMAGNETIC WATER TREATMENT (EWT) TO REDUCE HEAVY METALS IN PIT LAKE - Veny Luvita; Novan Agung Mahardiono; Hanif Fakhrurroja; Edy Tanu; Anto Tri Sugiarto (Instrumentasi, 2019)
Mining areas in Indonesia still use water sources from the pit lake, called Kolong. Kolong is raw water material of the water local company (PDAM) in obtaining clean water. The lake water usually processed with chemical and physicsmethods before distributed to the community. Whereas in fact the former mine lake water has a heavy metal content that is still relatively high. In mining areas, river and lake water are still polluted by heavy metals that harm living things that can not be decomposed directly by microorganisms naturally and even require a relatively long time to process them. Processed by using Advanced Oxidation Processes (AOPs) and Electromagnetic Water Treatment (EWT) become one of the processing alternatives by removing the heavy metals. The advantage of using this method is high efficiency, ability to process will not cause another waste andincluding as clean technology. The aim of this research activity is to test integrated water treatment system using the physical and chemical method by utilizing surface water contaminated by heavy metals through a combination of advanced oxidation technology and electromagnetic water treatment for physics-chemical water quality improvement which can be utilized by PDAM as raw water to get clean water. This research comparing no processing water, processing water with AOPs and EWT, then combining AOPs-EWT. The result of heavy metal removal in water can be reduced up to ± 90%.